The metamorphosis of U.S.-Korea relations the Korean question revisited - Han, Jongwoo, 1962- (Lexington studies on Korea's place in international relations, 2022)
"In tracing the history of U.S./Korea encounters, this book stresses that as America opened a Pandora Box with an initial raid, thereby unleashing the "Korean Question," the United States now needs to uphold its initial peaceful treaty commitment by normalizing relations with Pyeongyang, thus bringing closure to the "Korean Question.""--